Professional and Soldiers: Measuring Professionalism in the Thai Military - RICKS, Jacob Isaac (Institutional Knowledge at Singapore Management University, 2014)
Thailand’s military holds an important place in the political sphere and has done so since the fall of the absolute monarchy in 1932. Events in recent years demonstrate that, after over a decade of declining political influence, the military has reclaimed its role as one of the major pillars of Thai politics. This raises questions as to how military officers see themselves and how they envision the military’s role in Thailand. Utilizing data from a new survey of over 500 military officers, we evaluate the attitudes of Thai soldiers. Pairing these findings with interviews, we furnish a robust picture of how members of the military view their organization as well as its relationship to Thai society.